EFL Students’ Perception on Using Storybookscanada.ca as Autonomous English Learning Activity at English Department FBS UNP - F, Zhafira Ramadhani; Marlina, Leni (Universitas Negeri Padang, 2024)
Children's digital literature may be used as an innovative learning tool for reading and listening. The aim of this research is to reveal students’ perceptions on using digital children’s literature storybookscanada.ca as autonomous learning activity. This researcher uses descriptive research with quantitative approach. The population of this research were students of Introduction to Literature classes, English Department, FBS, Universitas Negeri Padang (UNP). Data was collected from 27 students using a questionnaire with 20 closed statements using 4 Likert scales, and through an interview with 5 key questions about students' perceptions of using digital children's literature storybookscanada.ca. the result of this research from physical and psychological aspect. Firstly, from physical aspect the result showed that the majority of students like and enjoy reading and listening short stories from website storycanada with positive perception of their impact on comprehension, visual, auditory sense and enjoyment in learning English. The total average of students perception in the physical aspect (3.35) it means have very positive impact. Secondly, from the psychological aspect the results showed that the use of storyory.com significantly increased students' interest, self-confidence and engagement in English learning, reflecting the positive psychological impact. The total average of perception indicators in the psychological aspect is 3.36 (Positive). Since the students' perceptions on both physical and psychological aspects are very positive, the other classes are suggested to use storycanada in a similar way as an autonomous learning activity.